CALIBRATION OF ULTRASONIC FLOWMETER FOR WI-FI NETWORK WITH THE HELP OF WEB BROWSER - M. A. Velichko; Yu. P. Gladkikh; O. N. Satler (Вестник Дагестанского государственного технического университета: Технические науки)
Objectives. The purpose of the work was to change the method of signal transmission containing metrological information from industrial time-pulse ultrasonic gas flow meter to a compu-ting device (CD). It was planned to expand the range of devices serving as gas flow calculators. A hardware-software complex (HSC) for automatic calibration / verification of ultrasonic flowmeters was to be developed. This HSC should work equally well on different operating systems. The information exchange between the CD and the flowmeter was to be carried out wirelessly.Method. The Wi-Fi Pro-tocol was used as a wireless Protocol. The energy-efficient ESP8266 controller was chosen as micro-controller to provide the functionality of Wi-Fi. The ESP8266 board acted as a Wi-Fi access point on the network to which CD was connected for data exchange. The ESP8266 microcontroller also served as a HTTP server. Exchange of metrological and other information was carried out by GET-requests. Given the need for continuous flow measurements and simultaneous communication between the user and the flow meter, requests to the server were transmitted using AJAX technology. The software part of the APK consisted of 3 programs: a program that measured the flow and transmitted the information further to the ESP8266 microcontroller, a server program recorded in ESP8266, providing a response to the requests of CD users, and the client program installed on the CD. The article discusses the key points of the HSC.Result. As a result of this work, the HSC was processed for calibration/verification of ultrasonic gas flow meters. For the first time this process for industrial flow meters was implemented using the ESP8266Wi-Fi controller as an access point. As a WU, it became possible to use any desktop or laptop computer or mobile device with a modern browser.Conclusion. The method proposed in the paper significantly simplified the data exchange between the VU and the flowmeter, reduced the cost of software development due to the common approach for different operating systems.